Partisipasi Masyarakat Padang Panjang terhadap Kegiatan Literasi di Perpustakaan Daerah Kota Padang Panjang - Arsah, Kurnia; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThis paper discusses about the participation of the people of Padang Panjang towards the literacy activities in the library of Padang Panjang City. Writing this paper aims to: (1) describe the literacy activities that exist in the library area of Padang Panjang City; (2) to describe how people's participation in literacy activities in the library of Padang Panjang City; (3) to describe the constraints and solutions of literacy activities in the library of Padang Panjang City. Data were collected through observation, interview and documentation. Based on the results of the study, it can be concluded as follows: (1) literacy activities in the Padang Panjang City regional library vary, namely read shelf, endowments of books derived from the general public's contribution to pre-prosperous communities, and activities of creative classes namely, theater classes, storytelling classes, writing classes and storytelling classes; (2) the participation of the Padang Panjang community in literacy activities was welcomed enthusiastically by each activity and participated in every series of literacy activities in the Padang Panjang library; (3) the constraints and solutions faced by literacy activities in the Padang Panjang City library are inadequate facilities and infrastructure so that it needs to provide better facilities and infrastructure, as well as less interest in participating in literacy activities. after doing the activity of the literacy.Keyword: library, participation, literacy.